The Characteristics of Modernism in Ian McEwan's Atonement - Mehrnaz Khoshgam; Ariman Sitompul; Syarifuddin (Matondang Journal, 2024)
The study aims to find out the characteristics of modernism in Ian McEwan. the result of the study shows Ian McEwan's Atonement exemplifies the characteristics of modernism through its innovative narrative techniques, thematic explorations, and engagement with social critique and philosophical inquiry. The novel challenges traditional literary conventions, inviting readers to reconsider their perceptions of truth, memory, and human experience. By analyzing McEwan's use of stream-of-consciousness narration, fragmentation, and non-linear narrative structure, along with his exploration of themes such as truth, war, class, and morality, this essay has demonstrated how Atonement fits within the broader scope of modernist literature. McEwan's novel continues to resonate with readers, offering profound insights into the complexities of human nature and the enduring legacy of modernist experimentation in contemporary literature.